PENGARUH MEDIA SOSIAL TIKTOK TERHADAP MORAL PESERTA DIDIK KELAS X - Rafli, Mochamad; Fitriyadi, Dinar Sugiana; Lestari, Ria Yuni (UNTIRTA CIVIC EDUCATION JOURNAL, 2025)
Tiktok is blocked in various countries because it contains racial, hate speech and suicide content so that it can affect the moral conditions and behavior of users. the research method used in this study is quantitative using a correlation study approach and a survey to collect the data. The respondents involved were 63 people, namely class X students. the results and analysis obtained are that Tiktok social media has an influence on student morale of 14.8% and is in the very low category. there are other factors that influence outside the factors studied. Tiktok social media can have an influence on the morale of students but there are more decisive factors in the formation of student morale, such as environment, family and peers.